Semantics development dynamics of the term marriage in the Ukrainian family law - Бортнік, Ганна Григорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article deals with the central element of the family law term system – the term marriage, the stages of its semantics formation in the language of the Ukrainian legislation from 1920s till the current period, besides the research gives characteristics to the analytical terms with the element marriage in their semantic saturation and paradigmatic relations.